PENGARUH GAYA KEPEMIMPINAN INKLUSIF TERHADAP KINERJA KARYAWAN, EFIKASI DIRI SEBAGAI VARIABEL MEDIASI PADA PT. GUMAS ALAM SUBUR - Yandri Andiko; Anike Retawati; Pratiwi Hamzah; Nurlia Eka Damayanti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
PT. Gumas Alam Subur is one of the companies that can improve employee performance through training and leadership development programs. This study aims to analyze the effect of inclusive leadership style on employee performance, with self-efficacy as a mediator. The approach used is quantitative-associative with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with the help of Smart Pls 3.0. Data were collected using a Likert scale questionnaire distributed to 134 employees at PT Gumas Alam Subur. The results of the study indicate that inclusive leadership style can have a positive and significant impact on employee performance. Inclusive leadership style can also increase self-efficacy, which then acts as a link in relation to improving employee performance. These findings confirm that to improve employee performance, PT Gumas Alam Subur not only needs to improve managerial leadership styles, but also prioritize efforts to enhance employee self-confidence, specifically self-efficacy, which serves as a key mechanism in building long-term commitment and loyalty toward the organization.